Mechanical Study of Paving Block Based on High Density Polyethylene (HDPE) Polymer With The Addition of Natural Fiber Filler (Rice Husk, Silica Sand and Sugar Cane Bagassa) - Syahdad Aziz; Mursalin Mursalin; Muh. Fachrul Latief; A. Indra Wulandari Ramadani; Setiawan Dewa Gede Eka; Idawati Supu (BULETIN FISIKA, 2026)
This research has succeeded in making HDPE polymer-based paving blocks with the addition of natural fiber fillers consisting of 3 types, namely rice husks, bagasse, and silica sand. The aim is to see the composition and mechanical properties of the best paving blocks with HDPE plastic waste as a polymer. The method used in this research is experimental, namely making paving blocks directly as the main approach, then analyzing their mechanical properties. The composition ratio between the polymer and the filler consists of 30%, 70%, 50%, 50% and 70%, 30%, respectively. The samples that were successfully made were then tested (compressive strength, porosity) and characteristic tests (Scanning Electron Microscope (SEM) and X-Ray Fluorescence (XRF).